Adherence and quality of life among diabetic patients with hypertension - Akrom Akrom; Wima Anggitasari (Intelektual Pustaka Media Utama, 2019)
The level of treatment adherence and quality of life are not known in diabetic patients with hypertension. The study aim was to evaluate the level of adherence and quality of life of diabetic patients with hypertension in Bantul Public Hospital (BPH), Bantul, Indonesia.This study used a Cross-sectional method by conducting a survey through a direct interview with the patient. Participants of this study were 143 diabetic patients with hypertension in the internal disease clinic of BPH. Modified Morisky Medication Adherence Scale was used to measure the level of treatment adherence and SF36 questionnaires were used to measure the quality of life. Descriptive and analytical statistical was performed on data from the adherence assessment, quality of life, demographic characteristic and the clinical condition of the research participant. Bivariate analysis with Chi-square was performed to assess the relationship between demographic and clinical factors to the high level of adherence. The majority of respondents had moderate and low levels of adherence. There were 34 patients (23.78%) with a high level of adherence, 56 patients (39.16%) with moderate level of adherence, and 53 patients (37.06%) with low level of adherence. Respondents also had low quality of life, in which the average score of quality of life was 61.96±12.48. Male and college-educated patients have higher adherence (OR>1, p<0.05) compared to other groups. Medication adherence and quality of life of diabetic patients with hypertension in BPH were relatively low. Male and high college-educated patients were associated with high levels of adherence